Psikologi Islam, Pseudo Ilmiah? - Rahayu, Iin Tri (el Harakah: Jurnal Budaya Islam, 2002)
As a religion, Islam not only offers a system of belief, worship, and ethics, but further, Islam has embraced all cultures and civilizations. This also includes culture and scientific civilization. In the span of the history of culture and civilization, Islamic discourse is never silent from psychology, from basic principles, physiological concepts, to operational techniques. Method of study and development of Islamic psychology pursued through two ways namely pragmatic method and idealistic method. This paper describes mapping methods and approaches of Islamic psychology as well as research method and development of Islamic psychology. The result shows that Islamic psychology is no longer in pseudo scientific level but it has exceeded the scientific boundaries. The objectivity of a science is only a matter of agreement, whose criteria are both quantitative and qualitative. Contemporary psychology has gained agreement from its own circle. Likewise Islamic psychology has gained agreement from the Muslims. Sebagai agama, Islam tidak saja menawarkan sistem kepercayaan, peribadatan, dan etika, tetapi lebih jauh, Islam telah mencakup seluruh kebudayaan dan peradaban. Termasuk di dalamnya yaitu kebudayaan dan peradaban ilmiah. Dalam rentang sejarah kebudayaan dan peradaban, wacana Islam tidak pernah sunyi dari pembahasan psikologi, mulai dari prinsip-prinsip dasar, konsep- konsep fisiologis, sampai pada teknik operasionalnya. Metode pengkajian dan pengembangan psikologi Islam ditempuh melalui dua cara yaitu metode pragmatis dan metode idealistik. Tulisan ini menjabarkan pemetaan metode dan pendekatan psikologi Islam serta metode pengkajian dan pengembangan psikologi Islam. Hasil yang diperoleh yaitu psikologi Islam bukan lagi bertaraf pseudo ilmiah tetapi telah melampaui batas-batas ilmiah. Objektivitas suatu ilmu hanyalah persoalan kesepakatan, yang kriterianya bukan hanya kuantitatif tetapi juga kualitatif. Psikologi kontemporer telah mendapatkan kesepakatan dari kalangannya sendiri. Demikian juga psikologi Islam telah mendapatkan kesepakatan dari kalangan kaum Muslim.